Classical mechanics of dipolar asymmetric top molecules in collinear static electric and nonresonant linearly polarized laser fields: energy-momentum diagrams, bifurcations and accessible configuration space (2008)
We study classical energy-momentum ($E$-$m$) diagrams for rotational motion of dipolar asymmetric top molecules in strong external fields. Static electric fields, nonresonant linearly polarized laser fields, and collinear combinations of the two are investigated. We treat specifically the molecules iodobenzene (a nearly prolate asymmetric top), pyridazine (nearly oblate asymmetric top), and iodopentafluorobenzene (intermediate case). The location of relative equilibria in the $E$-$m$ plane and associated bifurcations are determined by straightforward calculation, with analytical results given where possible. In cases where analytical solutions cannot be obtained, we resort to numerical solutions, while keeping a geometrical picture of the nature of the solutions to the fore. The classification we obtain of the topology of classically allowed rotor configuration space regions in the $E$-$m$ diagram is of potential use in characterization of energy eigenstates of the corresponding quantum mechanical problem.